Intravenous procedural sedation: an alternative in the treatment of patients with intellectual disability - Barbieri, Cíntia Megid; Gomes, Alessandra Cristina; Menezes, Taís Elisabete Crivellaro de; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (My University, 2010)
Conscious sedation has become established as an important alternative to general anesthesia (GA) in dental treatment of patients with intellectual disability (ID). Aim: to investigate dental patients undergoing sedation using a mean dose of 0.6 mg/kg intravenous midazolam and the adverse events of sedation in patients with ID. Methods: This study analyzed the records of 163 dental patients with ID aged between 2 and 76 years who had undergone conscious intravenous sedation (CIV) using a mean dose of 0.61 mg/kg of midazolam at Araçatuba Dental School, São Paulo State University, Brazil. The efficacy and complications induced by CIV were evaluated in each subject. Results: CIV was effective for dental treatment in 80% of the cases. A total of 626 dental procedures were performed. The mean treatment time was 33.9 minutes. There was statistically significant difference (p<0.05) between absence and presence of adverse reactions. Adverse reactions were observed in 21.47% of the cases. Conclusions: The results of this study showed that CIV is a useful method for dental treatment of patients with ID and these patients can need higher doses of sedative to reach an adequate level of sedation.
Keywords: Dental anesthesia; Dental care; Intellectual disability; Sedation